Fitotestes para avaliação de risco toxicológico de cério em solos - Pereira, Thaísa Aparecida Resende (2019)
Cerium (Ce) is an element from the lanthanide family. It is considered one of the most abundant "rare-earth element" (REE) in Earth's crust. Mainly, it is found in rocks like carbonatite, and it has many technological applications including fertilizers. As it is strongly exploited, it could be accumulate in the environment and becomes a potentially toxic element for plants and other living beings. When present in the soil, Ce can be absorbed by plants and cause negative alterations in germination, plants growth and at the cellular level. However, the effects of Ce need to be better elucidated. In this sense, the objective of this work was to evaluate the eco(geno)toxicological effects of cerium through bioassays in the plant models Lactuca sativa L., Allium cepa L., Pennisetumglaucum L. and Phaseolus vulgaris L. The seeds were exposed to crescent doses of Ce (0.50, 85, 144.5, 245.7, 417.6, 709.9, 1206.9 and 2051.7 mg kg-1) mixed to Oxisol, Inceptsol and Artificial soil samples, and arranged in Petri dishes. The Petri dishes were conditioned in a B.O.D. (BiochemestryOxigen Demand) incubator at 24 ° C, without photoperiod, for 96 hours. Then, macroscopic analyzes were performed for all species (germination and growth) and microscopic for A. cepa.Germination and IVG values varied according to the species and type of soils tested. In general, lettuce seeds had germination negatively affected (Tukey p <0.05) by the different Ce doses when exposed to contaminated Oxisol and Inceptsol. The higher doses of Ce significantly reduced the growth of the seedlings of the four models in the three types of soils, being the most expressive reduction in Oxisol. It was observed that these growth results corroborate with fresh matter data. The MI of A. cepacells presented differences in relation to the control, being higher only at doses of 50, 144.5, 245.7 and 417.6 mg kg-1 of Ce in Oxisol. Ce did not induce significant alterations in the cell cycle of meristematic cells, however, in cells of the F1 region led to the formation of MCN in the highest concentrations, showing mutagenic effect. Therefore, it is possible to conclude that Oxisol containing Ce has a higher potential to induce phytotoxicity due to the possible higher phyto-availability of Ce in this soil. Lactuca sativa showed higher sensitivity when germinated in Ce treated soils, while Allium cepa presented low germination in Oxisol and Inceptsol.